A high-strength refractory material and its preparation method and application

By using materials such as electromelting corundum and designing special cracking agents and fusion agents, the problem of insufficient performance and service life of existing sewer bricks is solved, and the preparation of high-strength refractory materials is realized, which significantly improves thermal shock resistance and corrosion resistance, and meets the high-performance needs of the steelmaking continuous casting process.

CN118184323BActive Publication Date: 2025-03-21HANDAN GUIQIANHENG MASCH MFG CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410314627.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-19
Publication Date
2025-03-21
Estimated Expiration
2044-03-19

AI Technical Summary

Technical Problem

The existing aluminum-carbon and aluminum-magnesium carbon-based materials have poor performance, service life and safety, making it difficult to meet the needs of wear resistance, oxidation resistance, thermal shock resistance and erosion resistance during continuous casting of steelmaking.

Method used

Electromel corundum, high alumina bauxite clinker, metal silicon powder, anti-cracking agent, titanium aluminum carbide, titanium carbide and phenolic resin are used as raw materials, and then sintered by premixing and pressing to form and sintering agents. Special anti-cracking agents and fusion agents are designed to improve the thermal shock resistance and corrosion resistance of the material.

Benefits of technology

It significantly improves the thermal shock resistance, corrosion resistance and strength of the material, extends the service life, reduces the cost of replacement and maintenance, and improves the safety and efficiency during continuous casting of steelmaking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004748559150000111
    Figure BDA0004748559150000111
Patent Text Reader

Abstract

A high-strength refractory material and its preparation method and application, belonging to the technical field of refractory materials, the raw materials of the refractory material include fused corundum, high-alumina bauxite clinker, metal silicon powder, anti-cracking agent, titanium aluminum carbide and titanium carbide, etc., wherein the anti-cracking agent is prepared by modifying boron phenolic resin, mesophase asphalt, artificial graphite powder and silicon carbide fiber. The refractory material of the present invention adopts metal silicon powder to improve wear resistance and oxidation resistance, titanium aluminum carbide to improve oxidation resistance, titanium carbide to improve strength, and anti-cracking agent after surface modification and film formation to greatly improve thermal shock resistance and reduce thermal expansion rate and slag erosion rate. In addition, adding titanium aluminum carbide can improve strength and thermal shock resistance to a certain extent, has good oxidation resistance, and improves erosion resistance. The refractory material can be used for high carbon steel and low carbon steel, and is particularly suitable for casting high oxygen steel, calcium treated steel and high manganese steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a high-strength refractory material and a preparation method thereof and an application thereof as a drain brick. Background Art

[0002] With the development of steelmaking continuous casting technology, as well as the development needs of cost reduction, efficiency improvement and high quality, all process links and consumables of steelmaking continuous casting need to improve efficiency and quality. Among them, the flow control of molten steel during the casting process of the continuous casting machine requires the support of the sliding nozzle system. The sliding nozzle system has good controllability and can improve the efficiency of steelmaking production; the sliding nozzle is generally composed of a sliding control mechanism, an upper nozzle, an upper slide plate, a lower slide plate and a lower nozzle. The upper nozzle and the upper slide plate are stationary, and the lower slide plate and the lower nozzle are combined as sliding parts. Therefore, the lower nozzle is in direct contact with the high-temperature molten steel, and is subjected to scouring and high-temperature oxidation. It is necessary to have high oxidation resistance, corrosion resistance, scouring resistance, high-temperature thermal shock stability, crack resistance, and need to reduce the pollution of molten steel. If the performance is poor, it will be cracked due to thermal stress, and the molten steel will penetrate the steel along the cracks. In severe cases, it will cause steel leakage or explosion accidents.

[0003] Aluminum-carbon and aluminum-magnesium-carbon materials are commonly used materials for nozzle bricks. Since nozzle bricks are consumables, in order to reduce costs, the material of nozzle bricks is inferior to that of slide bricks. Therefore, when continuously casting low-carbon steel, high-oxygen steel, calcium-treated steel or high-manganese steel, there are problems such as easy oxidation, poor corrosion resistance, poor scouring resistance, poor high-temperature thermal shock stability, and easy cracking. It will also shorten the service life and reduce safety, thereby increasing the cost of replacement and maintenance. Therefore, with the continuous improvement of the quality requirements of metal smelting and the goal of reducing costs and increasing efficiency, it is also necessary to continuously improve the performance, service life and safety of nozzle bricks. Summary of the invention

[0004] The existing drain bricks made of ordinary aluminum-carbon and aluminum-magnesium-carbon materials have relatively poor performance, service life and safety, and it is difficult to make breakthrough improvements. The present invention provides a high-strength refractory material and its preparation method and application, which uses fused corundum, high-alumina bauxite clinker, metal silicon powder, anti-cracking agent, titanium aluminum carbide, titanium carbide and phenolic resin as raw materials; that is, metal silicon powder is used to improve wear resistance and oxidation resistance, titanium aluminum carbide is used to improve oxidation resistance, and titanium carbide is used to improve strength. An anti-cracking agent with special components is also designed and added. The anti-cracking agent has good surface modification and fusion after film formation, greatly improves thermal shock resistance, and reduces thermal expansion rate and slag erosion rate. In addition, the addition of titanium aluminum carbide can improve strength and thermal shock resistance to a certain extent, has good oxidation resistance, and improves erosion resistance. The specific technical scheme is as follows:

[0005] A high-strength refractory material is made of the following raw materials in parts by mass: 60 to 80 parts of fused corundum, 10 to 30 parts of high-alumina bauxite clinker, 3 to 6 parts of metal silicon powder, 4 to 8 parts of anti-cracking agent, 2 to 5 parts of titanium carbide aluminum, 1 to 5 parts of titanium carbide and 3 to 8 parts of phenolic resin;

[0006] The preparation method of the anti-cracking agent is as follows: according to the mass ratio of boron phenolic resin: mesophase asphalt: artificial graphite powder: silicon carbide fiber: fusion agent = (5-10): (0.3-0.5): (4-8): (5-10): (0.3-4), the boron phenolic resin and the silicon carbide fiber are uniformly mixed to obtain material A; the artificial graphite powder and the mesophase asphalt are uniformly mixed, and then modified at 360° C. to 400° C. and 60 r / min to 80 r / min for 2h to 2.5h, and cooled to obtain material B; the material A, the material B and the fusion agent are uniformly mixed, and dried to obtain the anti-cracking agent;

[0007] The fusion agent is a carboxymethyl chitosan-trimethylsiloxysilicate aqueous solution, and the mass ratio is water: carboxymethyl chitosan: trimethylsiloxysilicate = 100: (2-5): (5-10).

[0008] In the above technical solution, the composition of the fused corundum is in the following proportions by mass: 3 to 8 parts for particle size 0.01 mm < ≤ 0.3 mm, 15 to 25 parts for particle size 0.3 mm < ≤ 1.5 mm, and 20 to 30 parts for particle size 1.5 mm < ≤ 3 mm.

[0009] In the above technical solution, the high alumina clinker contains AL 2 O 3 The mass content is above 90%; the composition of the high-alumina bauxite clinker is in the following mass proportions: 0.01mm<particle size≤1mm is 3 to 8 parts, 1mm<particle size≤3mm is 10 to 15 parts.

[0010] In the above technical solution, the particle size of the metallic silicon powder is less than 90 μm.

[0011] In the above technical solution, the particle size of the titanium aluminum carbide is less than 150 μm.

[0012] In the above technical solution, the particle size of the titanium carbide is less than 90 μm.

[0013] In the above technical solution, the mass content of free phenol in the boron phenolic resin is less than 7%; the particle size of the boron phenolic resin is 50 μm to 300 μm.

[0014] In the above technical solution, the artificial graphite powder is obtained by graphitizing calcined petroleum coke at 2800°C to 3000°C, and the median particle size of the artificial graphite powder is 15μm to 30μm.

[0015] In the above technical solution, the median particle size of the mesophase asphalt is less than 5 μm.

[0016] In the above technical solution, the length of the silicon carbide fiber is 1 mm to 3 mm.

[0017] The above-mentioned method for preparing a high-strength refractory material comprises the following steps:

[0018] S1: Premix metal silicon powder, titanium carbide and titanium carbide uniformly by mass to obtain premixed auxiliary materials; mix fused corundum, high-alumina bauxite clinker and premixed auxiliary materials uniformly, and finally add anti-cracking agent and phenolic resin for mixing, place in a trapped material chamber, heat and dehumidify, and after trapped for 10 to 15 days, use a 500-ton to 650-ton press to press and form, and after cooling, obtain a brick;

[0019] S2: sinter the bricks at 1500°C to 1650°C for 2h to 3h to obtain high-strength refractory materials.

[0020] The high-strength refractory material is used to make downspout bricks and is used for steelmaking and continuous casting of high-carbon steel, low-carbon steel, high-oxygen steel, calcium-treated steel or high-manganese steel.

[0021] Compared with the prior art, the high-strength refractory material and the preparation method and application thereof of the present invention have the following beneficial effects:

[0022] 1. The refractory material of the present invention uses fused corundum, high-alumina bauxite clinker, metal silicon powder, anti-cracking agent, titanium aluminum carbide, titanium carbide and phenolic resin as raw materials; wherein the metal silicon powder has good wear resistance and oxidation resistance, titanium aluminum carbide is Ti 3 AlC 2 , has good oxidation resistance, and titanium carbide can enhance strength. Among them, a special composition of anti-cracking agent is designed, which has very outstanding anti-cracking performance, thermal shock resistance and erosion resistance.

[0023] Second, the present invention designs a preparation method of an anti-cracking agent, using boron phenolic resin, mesophase asphalt, artificial graphite powder and silicon carbide fiber as raw materials, designing a certain ratio, mixing the boron phenolic resin and silicon carbide fiber, so that the boron phenolic resin is dispersed and attached to the surface of the silicon carbide fiber, and in the subsequent heat treatment, the fusion of the silicon carbide fiber and other components can be enhanced, and the boron phenolic resin with a phenol mass content of less than 7% has a high heat resistance, and the heat treatment bonding strength is relatively high, achieving a good anti-cracking effect. Artificial graphite powder and mesophase asphalt are evenly mixed, and then stirred and modified at 360℃~400℃ for 2h~2.5h, so that the surface of the artificial graphite powder is coated with the carbonized mesophase asphalt to form a core-shell structure, and the viscosity of the artificial graphite powder combined with other components is improved, so as to achieve a good anti-cracking effect. After the two are coated and modified, they are mixed, the dispersion homogeneity is better, and fiber agglomeration or micro-powder agglomeration will not occur. The obtained anti-cracking agent can greatly improve the thermal shock resistance and erosion resistance of refractory materials.

[0024] 3. The present invention adopts carboxymethyl chitosan-trimethylsiloxysilicate fusion agent, and the film formation changes the surface properties of the anti-cracking agent component, and the fusion with other components is better. After film formation, it is easier to mix evenly, improves homogeneity, and improves thermal shock resistance and corrosion resistance.

[0025] 4. The anti-cracking agent of the present invention is designed with respect to the combination characteristics of fused corundum, high-alumina bauxite clinker, metallic silicon powder, titanium aluminum carbide and titanium carbide in terms of its composition and proportion. In particular, the combination of titanium aluminum carbide and metallic silicon powder is relatively poor and they are prone to cracking. By using boron phenolic resin and mesophase asphalt anti-cracking components, the bonding of the brick blank can be ensured, the crack resistance of the brick blank can be ensured, the thermal shock resistance can be improved, and the slag erosion rate can be reduced.

[0026] 5. In the method for preparing the refractory material of the present invention, it is designed that the metallic silicon powder, titanium aluminum carbide and titanium carbide are first premixed evenly, which can disperse the auxiliary materials well, prevent small-particle components from agglomerating, and shorten the subsequent mixing time with large-particle components (electrofused corundum, high-alumina bauxite clinker). It is designed that the anti-cracking agent and phenolic resin are added at the end for mixing, which can protect the structure of the anti-cracking agent component from being destroyed in large quantities to the greatest extent, and always retain a part of the boron phenolic resin attached to the surface of the silicon carbide fiber, thereby ensuring the core-shell structure of the artificial graphite powder and the intermediate phase asphalt.

[0027] 6. Designing trapped materials for 10 to 15 days can remove moisture and gas, improve deposition density, and increase the density of pressed bricks. Firing the bricks at 1500℃ to 1650℃ for 2 to 3 hours can well fuse the materials and bring into play the performance of the anti-cracking agent, so that the boron phenolic resin can be well cured and the intermediate phase asphalt can be carbonized, which can improve the bonding compactness between the material components, improve crack resistance and thermal shock resistance, reduce thermal expansion rate and slag erosion rate; especially the thermal shock resistance is greatly improved, and there is no deep crack after more than 15 times.

[0028] In summary, the refractory material of the present invention adopts metal silicon powder to improve wear resistance and oxidation resistance, adopts titanium carbide to improve oxidation resistance, and adopts titanium carbide to improve strength. In particular, the anti-cracking agent with special components is designed to improve thermal shock resistance and reduce thermal expansion rate and slag erosion rate. In addition, the addition of titanium carbide can improve strength and thermal shock resistance to a certain extent, has good oxidation resistance, and improves corrosion resistance. The refractory material can be used for high carbon steel and low carbon steel, and is particularly suitable for the casting of high oxygen steel, calcium treated steel and high manganese steel, and has good practical value. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific implementation cases, but the present invention is not limited to these embodiments.

[0030] Example 1

[0031] A high-strength refractory material is made of the following raw materials by mass: 70 parts of fused corundum, 20 parts of high-alumina bauxite clinker, 5 parts of metal silicon powder, 6 parts of anti-cracking agent, 3 parts of titanium carbide, 3 parts of titanium carbide and 5 parts of phenolic resin. The composition of fused corundum is 5 parts by mass, 0.01mm < particle size ≤ 0.3mm, 20 parts by mass, 1.5mm < particle size ≤ 3mm, and 25 parts by mass. 2 O 3 The mass content is 92.3%; the composition of the high-alumina clinker is 5 parts by mass proportion for particles 0.01mm<particle size≤1mm, and 12 parts for particles 1mm<particle size≤3mm. The particle size of the metal silicon powder is less than 90μm. The particle size of the titanium carbide aluminum is less than 150μm. The particle size of the titanium carbide is less than 90μm.

[0032] Among them, the preparation method of the anti-cracking agent is: according to the mass ratio, boron phenolic resin: mesophase asphalt: artificial graphite powder: silicon carbide fiber: fusion agent = 8:0.4:6:6:2, 50μm~300μm boron phenolic resin and silicon carbide fiber with a length of 1mm~3mm are uniformly mixed to obtain material A; artificial graphite powder with a median particle size of 21.3μm and mesophase asphalt with a median particle size of 2.6μm are uniformly mixed, and then modified at 380℃ and 65r / min for 2h, and cooled to obtain material B; material A, material B and fusion agent are uniformly mixed and dried to obtain an anti-cracking agent; the fusion agent is a carboxymethyl chitosan-trimethylsiloxy silicate aqueous solution, and the mass ratio is water: carboxymethyl chitosan: trimethylsiloxy silicate = 100:3:8.

[0033] The free phenol content in the boron phenolic resin is 6.4%. The artificial graphite powder is obtained by graphitizing calcined petroleum coke at 3000°C.

[0034] The above-mentioned method for preparing a high-strength refractory material comprises the following steps:

[0035] S1: Premix metal silicon powder, titanium carbide and titanium carbide uniformly by mass to obtain premixed auxiliary materials; mix fused corundum, high-alumina bauxite clinker and premixed auxiliary materials uniformly, and finally add anti-cracking agent and phenolic resin for mixing, place in a trapped material chamber, heat and dehumidify, and after trapped for 12 days, use a 600-ton press to press and form to obtain a brick;

[0036] S2: The bricks are fired at 1600℃ for 2h and cooled to obtain high-strength refractory materials.

[0037] The high-strength refractory material is used to make downspout bricks and is used for steelmaking and continuous casting of high-carbon steel, low-carbon steel, high-oxygen steel, calcium-treated steel or high-manganese steel.

[0038] Example 2

[0039] A high-strength refractory material is made of the following raw materials by weight: 60 parts of fused corundum, 10 parts of high-alumina bauxite clinker, 3 parts of metal silicon powder, 4 parts of anti-cracking agent, 2 parts of titanium carbide, 1 part of titanium carbide and 3 parts of phenolic resin. The composition of fused corundum is 3 parts by weight, 0.01mm < particle size ≤ 0.3mm, 15 parts by weight, 1.5mm < particle size ≤ 3mm, and 20 parts by weight. 2 O 3 The mass content is 93.1%; the composition of the high-alumina clinker is 3 parts by mass proportion of 0.01mm<particle size≤1mm, 10 parts by mass proportion of 1mm<particle size≤3mm. The particle size of the metal silicon powder is less than 90μm. The particle size of the titanium carbide aluminum is less than 150μm. The particle size of the titanium carbide is less than 90μm.

[0040] Among them, the preparation method of the anti-cracking agent is: according to the mass ratio of boron phenolic resin: mesophase asphalt: artificial graphite powder: silicon carbide fiber: fusion agent = 5:0.3:4:5:1, 50μm~300μm boron phenolic resin and silicon carbide fiber with a length of 1mm~3mm are uniformly mixed to obtain material A; artificial graphite powder with a median particle size of 15μm and mesophase asphalt with a median particle size of 1.2μm are uniformly mixed, and then modified at 360℃ and 60r / min for 2h, and cooled to obtain material B; material A, material B and fusion agent are uniformly mixed and dried to obtain the anti-cracking agent; the fusion agent is a carboxymethyl chitosan-trimethylsiloxy silicate aqueous solution, and the mass ratio is water: carboxymethyl chitosan: trimethylsiloxy silicate = 100:2:5.

[0041] The free phenol content in the boron phenolic resin is 6.2%. The artificial graphite powder is obtained by graphitizing calcined petroleum coke at 2800°C.

[0042] The above-mentioned method for preparing a high-strength refractory material comprises the following steps:

[0043] S1: Premix metal silicon powder, titanium carbide and titanium carbide uniformly by mass to obtain premixed auxiliary materials; mix fused corundum, high-alumina bauxite clinker and premixed auxiliary materials uniformly, and finally add anti-cracking agent and phenolic resin for mixing, place in a trapped material chamber, heat and dehumidify, and after trapped for 10 days, use a 500-ton press pressure to press and form to obtain a brick;

[0044] S2: The bricks are fired at 1500°C for 2 hours and cooled to obtain high-strength refractory materials.

[0045] The high-strength refractory material is used to make downspout bricks and is used for steelmaking and continuous casting of high-carbon steel, low-carbon steel, high-oxygen steel, calcium-treated steel or high-manganese steel.

[0046] Example 3

[0047] A high-strength refractory material is made of the following raw materials by weight: 65 parts of fused corundum, 15 parts of high-alumina bauxite clinker, 4 parts of metal silicon powder, 5 parts of anti-cracking agent, 2.5 parts of titanium carbide, 2 parts of titanium carbide and 4 parts of phenolic resin. The composition of fused corundum is 4 parts by weight, 0.01mm < particle size ≤ 0.3mm, 18 parts by weight, 1.5mm < particle size ≤ 3mm, 22 parts by weight. 2 O 3 The mass content is 91.7%; the composition of the high-alumina clinker is 4 parts by mass proportion for particles 0.01mm<particle size≤1mm, and 12 parts for particles 1mm<particle size≤3mm. The particle size of the metal silicon powder is less than 90μm. The particle size of the titanium carbide aluminum is less than 150μm. The particle size of the titanium carbide is less than 90μm.

[0048] Among them, the preparation method of the anti-cracking agent is as follows: according to the mass ratio of boron phenolic resin: mesophase asphalt: artificial graphite powder: silicon carbide fiber: fusion agent = 6:0.35:5:6:1.5, 50μm~300μm boron phenolic resin and silicon carbide fiber with a length of 1mm~3mm are uniformly mixed to obtain material A; artificial graphite powder with a median particle size of 16.5μm and mesophase asphalt with a median particle size of 1.2μm are uniformly mixed, and then modified at 365℃ and 65r / min for 2h, and cooled to obtain material B; material A, material B and fusion agent are uniformly mixed and dried to obtain the anti-cracking agent; the fusion agent is a carboxymethyl chitosan-trimethylsiloxy silicate aqueous solution, and the mass ratio is water: carboxymethyl chitosan: trimethylsiloxy silicate = 100:2.5:6.

[0049] The free phenol content in the boron phenolic resin is 5.8%. The artificial graphite powder is obtained by graphitizing calcined petroleum coke at 2850°C.

[0050] The above-mentioned method for preparing a high-strength refractory material comprises the following steps:

[0051] S1: Premix metal silicon powder, titanium carbide and titanium carbide uniformly by mass to obtain premixed auxiliary materials; mix fused corundum, high-alumina bauxite clinker and premixed auxiliary materials uniformly, and finally add anti-cracking agent and phenolic resin for mixing, place in a trapped material chamber, heat and dehumidify, and after trapped for 11 days, use a 500-ton press pressure to press and form to obtain a brick;

[0052] S2: The bricks are fired at 1550°C for 2 hours and then cooled to obtain high-strength refractory materials.

[0053] The high-strength refractory material is used to make downspout bricks and is used for steelmaking and continuous casting of high-carbon steel, low-carbon steel, high-oxygen steel, calcium-treated steel or high-manganese steel.

[0054] Example 4

[0055] A high-strength refractory material is made of the following raw materials by mass: 75 parts of fused corundum, 25 parts of high-alumina bauxite clinker, 5.5 parts of metal silicon powder, 7 parts of anti-cracking agent, 4.5 parts of titanium carbide, 4 parts of titanium carbide and 6.5 parts of phenolic resin. The composition of fused corundum is 7 parts by mass, 0.01mm < particle size ≤ 0.3mm, 22 parts by mass, 1.5mm < particle size ≤ 3mm, and 28 parts by mass. 2 O 3The mass content is 92.5%; the composition of the high-alumina clinker is 7 parts by mass proportion for particles 0.01mm<particle size≤1mm, and 14 parts for particles 1mm<particle size≤3mm. The particle size of the metal silicon powder is less than 90μm. The particle size of the titanium carbide is less than 150μm. The particle size of the titanium carbide is less than 90μm.

[0056] Among them, the preparation method of the anti-cracking agent is as follows: according to the mass ratio of boron phenolic resin: mesophase asphalt: artificial graphite powder: silicon carbide fiber: fusion agent = 9:0.45:6.5:8:2.5, 50μm~300μm boron phenolic resin and silicon carbide fiber with a length of 1mm~3mm are uniformly mixed to obtain material A; artificial graphite powder with a median particle size of 26.4μm and mesophase asphalt with a median particle size of 4.6μm are uniformly mixed, and then modified at 390℃ and 70r / min for 2.5h, and cooled to obtain material B; material A, material B and fusion agent are uniformly mixed and dried to obtain the anti-cracking agent; the fusion agent is a carboxymethyl chitosan-trimethylsiloxy silicate aqueous solution, and the mass ratio is water: carboxymethyl chitosan: trimethylsiloxy silicate = 100:3:5.5.

[0057] The free phenol content in the boron phenolic resin is 5.6%. The artificial graphite powder is obtained by graphitizing calcined petroleum coke at 2900°C.

[0058] The above-mentioned method for preparing a high-strength refractory material comprises the following steps:

[0059] S1: Premix metal silicon powder, titanium carbide and titanium carbide uniformly by mass to obtain premixed auxiliary materials; mix fused corundum, high-alumina bauxite clinker and premixed auxiliary materials uniformly, and finally add anti-cracking agent and phenolic resin for mixing, place in a trapped material chamber, heat and dehumidify, and after trapped for 14 days, use a 650-ton press pressure to press and form to obtain a brick;

[0060] S2: The bricks are fired at 1600°C for 2.5 hours and cooled to obtain high-strength refractory materials.

[0061] The high-strength refractory material is used to make downspout bricks and is used for steelmaking and continuous casting of high-carbon steel, low-carbon steel, high-oxygen steel, calcium-treated steel or high-manganese steel.

[0062] Example 5

[0063] A high-strength refractory material is made of the following raw materials by weight: 80 parts of fused corundum, 30 parts of high-alumina bauxite clinker, 6 parts of metal silicon powder, 8 parts of anti-cracking agent, 5 parts of titanium carbide, 5 parts of titanium carbide and 8 parts of phenolic resin. The composition of fused corundum is 8 parts by weight, 0.01mm < particle size ≤ 0.3mm, 25 parts by weight, 1.5mm < particle size ≤ 3mm, 30 parts by weight. 2 O 3 The mass content is 93.4%; the composition of the high-alumina clinker is 8 parts by mass proportion for particles 0.01mm<particle size≤1mm, and 15 parts for particles 1mm<particle size≤3mm. The particle size of the metal silicon powder is less than 90μm. The particle size of the titanium carbide is less than 150μm. The particle size of the titanium carbide is less than 90μm.

[0064] Among them, the preparation method of the anti-cracking agent is as follows: according to the mass ratio of boron phenolic resin: mesophase asphalt: artificial graphite powder: silicon carbide fiber: fusion agent = 10:0.5:8:10:3, 50μm~300μm boron phenolic resin and silicon carbide fiber with a length of 1mm~3mm are uniformly mixed to obtain material A; artificial graphite powder with a median particle size of 30μm and mesophase asphalt with a median particle size of 2.6μm are uniformly mixed, and then modified at 400℃ and 80r / min for 2.5h, and cooled to obtain material B; material A, material B and fusion agent are uniformly mixed and dried to obtain the anti-cracking agent; the fusion agent is a carboxymethyl chitosan-trimethylsiloxy silicate aqueous solution, and the mass ratio is water: carboxymethyl chitosan: trimethylsiloxy silicate = 100:3.5:7.

[0065] The free phenol content in the boron phenolic resin is 6.3%. The artificial graphite powder is obtained by graphitizing calcined petroleum coke at 3000°C.

[0066] The above-mentioned method for preparing a high-strength refractory material comprises the following steps:

[0067] S1: Premix metal silicon powder, titanium carbide and titanium carbide uniformly by mass to obtain premixed auxiliary materials; mix fused corundum, high-alumina bauxite clinker and premixed auxiliary materials uniformly, and finally add anti-cracking agent and phenolic resin for mixing, place in a trapped material chamber, heat and dehumidify, and after trapped for 15 days, use a 650-ton press to press and form to obtain a brick;

[0068] S2: The bricks are fired at 1650°C for 3 hours and then cooled to obtain high-strength refractory materials.

[0069] The high-strength refractory material is used to make downspout bricks and is used for steelmaking and continuous casting of high-carbon steel, low-carbon steel, high-oxygen steel, calcium-treated steel or high-manganese steel.

[0070] Example 6

[0071] A high-strength refractory material is made of the following raw materials by mass: 80 parts of fused corundum, 15 parts of high-alumina bauxite clinker, 5 parts of metal silicon powder, 6 parts of anti-cracking agent, 3 parts of titanium carbide, 2 parts of titanium carbide and 7 parts of phenolic resin. The composition of fused corundum is 6 parts by mass, 0.01mm < particle size ≤ 0.3mm, 22 parts by mass, and 1.5mm < particle size ≤ 3mm. 2 O 3 The mass content is 94.6%; the composition of the high-alumina clinker is 4 parts by mass proportion for particles 0.01mm<particle size≤1mm, and 15 parts for particles 1mm<particle size≤3mm. The particle size of the metal silicon powder is less than 90μm. The particle size of the titanium carbide is less than 150μm. The particle size of the titanium carbide is less than 90μm.

[0072] Among them, the preparation method of the anti-cracking agent is as follows: according to the mass ratio, boron phenolic resin: mesophase asphalt: artificial graphite powder: silicon carbide fiber: fusion agent = 8:0.5:5:6:4, 50μm~300μm boron phenolic resin and silicon carbide fiber with a length of 1mm~3mm are uniformly mixed to obtain material A; artificial graphite powder with a median particle size of 18.6μm and mesophase asphalt with a median particle size of 2.5μm are uniformly mixed, and then modified at 360℃ and 75r / min for 2h, and cooled to obtain material B; material A, material B and fusion agent are uniformly mixed and dried to obtain the anti-cracking agent; the fusion agent is a carboxymethyl chitosan-trimethylsiloxy silicate aqueous solution, and the mass ratio is water: carboxymethyl chitosan: trimethylsiloxy silicate = 100:5:10.

[0073] The free phenol content in the boron phenolic resin is 5.1%. The artificial graphite powder is obtained by graphitizing calcined petroleum coke at 2800°C.

[0074] The above-mentioned method for preparing a high-strength refractory material comprises the following steps:

[0075] S1: Premix metal silicon powder, titanium carbide and titanium carbide uniformly by mass to obtain premixed auxiliary materials; mix fused corundum, high-alumina bauxite clinker and premixed auxiliary materials uniformly, and finally add anti-cracking agent and phenolic resin for mixing, place in a trapped material chamber, heat and dehumidify, and after trapped for 10 days, use a 650-ton press to press and form to obtain a brick;

[0076] S2: The bricks are fired at 1500°C for 3 hours and then cooled to obtain high-strength refractory materials.

[0077] The high-strength refractory material is used to make downspout bricks and is used for steelmaking and continuous casting of high-carbon steel, low-carbon steel, high-oxygen steel, calcium-treated steel or high-manganese steel.

[0078] Preparation Comparative Example 1

[0079] No anti-cracking agent is added to the refractory material, and other parameters are the same as in Example 1.

[0080] Preparation Comparative Example 2

[0081] No titanium carbide aluminum is added to the refractory material, and other parameters are the same as in Example 1.

[0082] Preparation Comparative Example 3

[0083] No anti-cracking agent and titanium carbide aluminum are added to the refractory material, and other parameters are the same as in Example 1.

[0084] Preparation Comparative Example 4

[0085] No boron phenolic resin is added as the anti-cracking agent in the refractory material, and other parameters are the same as those in Example 1.

[0086] Preparation Comparative Example 5

[0087] No fusing agent is added to the anti-cracking agent, and other parameters are the same as those in Example 1.

[0088] The size of the drain brick samples prepared in the above-mentioned Examples 1 to 6 and Comparative Examples 1 to 3 is: 230 mm×114 mm×65 mm. The performance of the drain brick samples was tested, and the results are shown in Table 1 below:

[0089] Table 1 Performance test results

[0090]

[0091] It can be seen from the above results that the samples of the drain bricks of Examples 1 to 6 have very good performance in terms of room temperature compressive strength, thermal shock resistance, thermal expansion rate, and slag erosion rate, especially the thermal shock resistance is greatly improved, and there is no deep crack for more than 15 times. The applicant speculates that the addition of a special component of an anti-cracking agent results in good crack resistance and good thermal shock resistance, thereby greatly reducing the slag erosion rate. Among them, the addition of titanium carbide aluminum can improve the strength and thermal shock resistance to a certain extent, has good oxidation resistance, and improves corrosion resistance. Good corrosion resistance can be used for high-carbon steel and low-carbon steel, especially for the casting of high-oxygen steel, calcium-treated steel, and high-manganese steel. In addition, the addition of boron phenolic resin can improve the bonding of titanium carbide aluminum and metal silicon powder to prevent cracking. The use of boron phenolic resin and mesophase asphalt can improve the bonding of the brick blank, improve thermal shock resistance, and reduce the slag erosion rate; but the samples without adding boron phenolic resin have relatively poor thermal shock resistance and slag erosion resistance. By using carboxymethyl chitosan-trimethylsiloxysilicate fusion agent, the film formation changes the surface properties of the anti-cracking agent component, and the fusion with other components is better. After film formation, it is easier to mix evenly, improves homogeneity, is easy to mix, and the trapped materials and pressed blocks are more compact, which improves the thermal shock resistance and corrosion resistance.

Claims

1. A high-strength refractory material, characterized in that: The invention is prepared from the following raw materials in parts by weight: 60 to 80 parts of fused corundum, 10 to 30 parts of high-alumina clinker, 3 to 6 parts of metal silicon powder, 4 to 8 parts of anti-cracking agent, 2 to 5 parts of titanium carbide aluminum, 1 to 5 parts of titanium carbide and 3 to 8 parts of phenolic resin; The preparation method of the anti-cracking agent is as follows: according to the mass ratio of boron phenolic resin: mesophase asphalt: artificial graphite powder: silicon carbide fiber: fusion agent = (5-10): (0.3-0.5): (4-8): (5-10): (1-4), the boron phenolic resin and the silicon carbide fiber are uniformly mixed to obtain material A; the artificial graphite powder and the mesophase asphalt are uniformly mixed, and then modified at 360°C-400°C and 60r / min-80r / min for 2h-2.5h, and cooled to obtain material B; the material A, the material B and the fusion agent are uniformly mixed, and dried to obtain the anti-cracking agent; The fusion agent is a carboxymethyl chitosan-trimethylsiloxysilicate aqueous solution, and the mass ratio is water: carboxymethyl chitosan: trimethylsiloxysilicate = 100: (2-5): (5-10); The free phenol content in the boron phenolic resin is less than 7% by mass; the particle size of the boron phenolic resin is 50 μm to 300 μm; the artificial graphite powder is obtained by graphitizing calcined petroleum coke at 2800° C. to 3000° C., and the median particle size of the artificial graphite powder is 15 μm to 30 μm; the median particle size of the mesophase asphalt is less than 5 μm; A method for preparing a high-strength refractory material comprises the following steps: S1: Premix metal silicon powder, titanium carbide and titanium carbide uniformly by mass to obtain premixed auxiliary materials; mix fused corundum, high-alumina bauxite clinker and premixed auxiliary materials uniformly, and finally add anti-cracking agent and phenolic resin for mixing, place in a trapped material chamber, heat and dehumidify, and after trapped for 10 to 15 days, use a 500-ton to 650-ton press to press and form, and after cooling, obtain a brick; S2: sinter the bricks at 1500°C to 1650°C for 2h to 3h to obtain high-strength refractory materials.

2. A high-strength refractory material according to claim 1, characterized in that: The composition of the fused corundum is in the following proportions by mass: 3 to 8 parts for a particle size of 0.01 mm < ≤ 0.3 mm, 15 to 25 parts for a particle size of 0.3 mm < ≤ 1.5 mm, and 20 to 30 parts for a particle size of 1.5 mm < ≤ 3 mm.

3. A high-strength refractory material according to claim 1, characterized in that: The mass content of Al2O3 in the high-alumina bauxite clinker is above 90%; the composition of the high-alumina bauxite clinker is in the following mass proportions: 3 to 8 parts for particles with a size of 0.01 mm < ≤ 1 mm, and 10 to 15 parts for particles with a size of 1 mm < ≤ 3 mm.

4. A high-strength refractory material according to claim 1, characterized in that: The particle size of the metal silicon powder is less than 90 μm; the particle size of the titanium aluminum carbide is less than 150 μm; and the particle size of the titanium carbide is less than 90 μm.

5. A high-strength refractory material according to claim 1, characterized in that: The length of the silicon carbide fiber is 1 mm to 3 mm.

6. Use of a high-strength refractory material according to any one of claims 1 to 5, characterized in that: High-strength refractory materials are used to make downspout bricks and are used for steelmaking and continuous casting of high-carbon steel, low-carbon steel, high-oxygen steel, calcium-treated steel or high-manganese steel.

Citation Information

Patent Citations

  • Alumina-carbon drain hole brick toughened with homogenizing material and production method thereof

    CN107473759A

  • High-toughness modified silicon corundum brick

    CN113526946A

  • Anti-erosion alkali-resistant brick

    CN114180947A

  • Preparation method of high-temperature-resistant thermal-shock-resistant composite magnesia carbon-based refractory brick

    CN117303925A

  • Refractory having excellent mechanical strength and spalling resistance, and method of manufacturing the same

    JP2005320196A